Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fphar.2022.765446
|View full text |Cite|
|
Sign up to set email alerts
|

Decreased Risk of Anxiety in Diabetic Patients Receiving Glucagon-like Peptide-1 Receptor Agonist: A Nationwide, Population-Based Cohort Study

Abstract: Background: Previous findings on using Glucagon-like peptide-1 receptor agonist (GLP1-RA) as an antidepressant were conflicting, lacking large-scale studies. We used population-based data to investigate depression and anxiety risk in diabetic patients receiving the medication.Methods: From claims records of the National Health Insurance Research Database (NHIRD) of Taiwan, we identified cohorts of 10,690 GLP1-RA users and 42,766 propensity score-matched patients without GLP1-RA use from patients with diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…This mechanism is effective in traditional antihyperglycemic agents, such as insulin or metformin, and the newer GLP-1 RAs [21]. Indeed, research has amply demonstrated that the use of GLP-1 RAs in T2DM patients is associated with a lower incidence of depression and anxiety compared to controls treated with different therapies [47,48,23]. In addition, recent studies evaluating the gut microbiota have suggested that one of the roles of GLP-1 RAs in treating anxiety is related to improved glucoregulation, leading to reduced proin ammatory cytokines and increased neuroprotection [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism is effective in traditional antihyperglycemic agents, such as insulin or metformin, and the newer GLP-1 RAs [21]. Indeed, research has amply demonstrated that the use of GLP-1 RAs in T2DM patients is associated with a lower incidence of depression and anxiety compared to controls treated with different therapies [47,48,23]. In addition, recent studies evaluating the gut microbiota have suggested that one of the roles of GLP-1 RAs in treating anxiety is related to improved glucoregulation, leading to reduced proin ammatory cytokines and increased neuroprotection [49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their metabolic effect, GLP-1 RAs have also shown relevant effects in mental health. In particular, an increasing amount of research focuses on GLP-1 RAs e cacy in reducing anxiety and depressive symptoms, highlighting an important connection between metabolic regulations and psychopathological mechanisms [20][21][22][23][24]. In fact, recent studies point out that disturbed homeostasis between the nervous system and the immune and endocrine systems, disturbances in cerebral energy metabolism, and dysfunction of the gut-brain axis could play an important role in the pathogenesis of depression and anxiety: GLP-1RAs, through a modulatory effect on the immune, endocrine, and metabolic processes in the central nervous system, appear to act actively in ameliorating these symptoms [20,25].…”
mentioning
confidence: 99%
“…Anti-hyperglycemic agents, such as metformin and GLP-1 RAs, have consistently shown to exert anti-depressive properties [ 21 ]. Indeed, there is wide evidence that the use of GLP-1 RAs in T2DM patients is associated with a lower incidence of depression and anxiety compared to controls treated with different therapies [ 23 , 48 , 49 ]. In addition, recent studies evaluating the gut microbiota have suggested that one of the roles of GLP-1 RAs in treating anxiety is related to improved glucoregulation, leading to reduced proinflammatory cytokines and increased neuroprotection [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2019 meta-analysis of 8 RCTs of individuals receiving GLP-1 agonists, GLP-1 agonists were associated with greater reduction in depressive symptoms compared with control treatments 8 . In a study using claim records from the National Health Insurance Research Database of Taiwan, 10,690 GLP-1 RA users were compared with 42,766 non-users matched by age, gender, index year, occupation, urbanization, comorbidities, and medications 9,10 . Compared with individuals not using GLP-1 RAs, those using GLP-1 RAs had a significantly reduced risk of anxiety and a moderate reduction of depression.…”
Section: Response From An Expertmentioning
confidence: 99%